Basic Profile of Early Childbirth in Mozambique - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
Measures of early childbirth are high in Mozambique. The share of women ages 18-22 who had a child before 18 is 39.0 percent and it has increased over time. The share of women who had a child before the age of 15, at six percent, has however decreased. Early childbirth is associated with lower wealth, lower education levels, and higher employment. These are however only correlations, not necessarily causal effects. In order to design programs and policies to reduce the prevalence of early childbirth, information is needed on its trend over time, where it is most prevalent in a country, and what the characteristics of girls giving birth early are.